PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN KOMUNIKASI VERBAL DAN KREATIVITAS BELAJAR PADA MATA DIKLAT TEKNOLOGI DASAR OTOMOTIF SISWA KELAS X SMK NEGERI 5 SURAKARTA TAHUN PELAJARAN 2014/2015 - Mulyono, Mulyono (Jurnal Nosel, 2015)
The objectives of this research are to improve: (1) the verbal communication of the students in Grade X of Automotive Engineering Department of State Vocational High School 5 of Surakarta through the application of the cooperative learning model of the STAD type in the education and training of Basic Automotive Technology in Academic Year 2014/2015, and (2) the learning creativity of the students in Grade X of Automotive Engineering Department of State Vocational High School 5 of Surakarta through the application of the cooperative learning model of the STAD type in the education and training of Basic Automotive Technology in Academic Year 2014/2015. This research used the classroom action research with two cycles. Each cycle consisted of four phases i.e. planning, implementation, observation, and reflection. Its subjects were the students in Grade X of Automotive Engineering Department B of the aforementioned school. The data sources of research were the teacher and students of the school. They were collected through observation, in-depth interview, and documentation and analyzed by using the descriptive quantitative technique of analysis. The results of research are as follows:  1) The application of the cooperative learning model of the STAD type could improve the verbal communication of the students in Grade in Grade X of Automotive Engineering Department B of State Vocational High School 5 of Surakarta on the learning materials of Work Cycle of Four-Stroke Gasoline Engine and Work Cycle of Four-Stroke Diesel Engine. In Cycle I, the percentage of the students who fulfilled the minimum learning completeness was 54.55%, and it became 70.23% in Cycle II. 2) The application of the cooperative learning model of the STAD type could improve the learning creativity of the students in Grade in Grade X of Automotive Engineering Department B of State Vocational High School 5 of Surakarta on the learning materials of Work Cycle of Four-Stroke Gasoline Engine and Work Cycle of Four-Stroke Diesel Engine. In addition, the percentage of the students who completed the criterion was 57.11% in Cycle I and became 71.52% in Cycle II. Thus, the application of the cooperative learning model of the STAD type could improve the verbal communication and learning achievement in the education and training of Basic Automotive Technology in Academic Year 2014/2015 of the students in Grade in Grade X of Automotive Engineering Department of State Vocational High School 5 of Surakarta in Academic Year 2014/2015.